Tricks of the ebay masters - Miller, Michael, 1958- (Que Pub., 2006)
Take the mystery out of eBay and the enviable PowerSellers. Tricks of the eBay Masters, Second Edition is full of advice and over 600 tricks from expert eBay users. They learned by doing and are now going to pass on their wisdom to you. Find out how to jazz up your auction listings with HTML, how to increase buyer traffic through key words and how to use photos to increase your selling potential. You'll even get tips on where to find items to sell, how to pack your items better and how to ship cheaply. Also find out what not to do as the experts give you examples of mistakes they made early in their eBay careers and how not to repeat them. Increase your auction income and successful bidding through Tricks of the eBay Masters, Second Edition .